Regional sustainability: Pressures and responses of tourism economy and ecological environment in the Yangtze River basin, China - Zhu, Kai; Zhou, Quan; Cheng, Yufeng; Zhang, Youtian; Li, Ting; Yan, Xiaoyue; Alimov, Atabek; Farmanov, Erkin; Dávid, Lóránt Dénes (Frontiers in Ecology and Evolution, 2023)
The relationship between the tourism economy and the ecological environment is under pressure, and balancing this relationship is crucial for promoting regional sustainability. In this study, the Yangtze River basin, the first largest river in Asia and third largest in the world, was selected as the focus area. The spatial and temporal characteristics of tourism economic development and ecological environmental pressure from 2000 to 2019 were analyzed using the tourism economic development index, ecological environmental pressure index and dynamic change index, and the decoupling process of tourism and the economic system was studied dynamically using the decoupling analysis model. The results show that (1) spatially, the tourism economy in the Yangtze River basin exhibits a pattern of high development in the east and low development in the west, and high in the south and low in the north. Ecological environmental pressures varied greatly, with less pressure in the upstream provinces and more pressure in the middle and downstream provinces. (2) Temporally, the tourism economies of Qinghai and Tibet started with a lower but faster growth rate, while Hunan and Hubei have a higher starting point but limited change. The ecological environmental pressure changes do not show a clear spatial distribution pattern. (3) The decoupling relationship between tourism economy and ecological environment in the Yangtze River basin is moving towards a harmonious development. Achieving a harmonious balance between the two systems is crucial for maintaining ecological balance and regional sustainability.